Factors Associated with Pregnant Women's Engagement in COVID-19 Vaccination - Putri, Desi Kurnia; Nursal, Dien Gusta Anggraini; Markolinda, Yessy; Masrizal, Masrizal (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: The Belimbing Community Health Centre in Padang City exhibits a limited level of engagement among pregnant women in the administration of Covid-19 vaccinations.Purpose : The objective of this study was to ascertain the factors associated with the engagement of pregnant women in the Covid-19 vaccine within the operational jurisdiction of the Belimbing Health Centre.Methods: The present study adopts a quantitative approach and employs a cross-sectional study design. The data collection period spans from January to June 2022, and the study is conducted within the operating area of the Belimbing Health Centre. The study sample consists of 93 pregnant women. The method employed for sampling in this study is simple random sampling.Results: The findings of the study indicated that a significant majority of the participants, specifically 87.1%, had completed the initial step of the Covid-19 vaccination process. The study explored the association between pregnant women's knowledge, attitudes, the role of health personnel, the involvement of husbands, socio-economic status, and their level of participation in Covid-19 immunisation. The findings of the multivariate analysis indicated that the variable with the greatest influence was the mother's readiness for pregnancy (p-value = 0.028; POR = 4.510). The participation of pregnant women in Covid-19 immunisation is influenced by various factors, including knowledge, attitudes, the role of health providers, the role of spouses, and socio-economic factors. The primary determinant is the attitude exhibited by pregnant mothers. There is an expectation that healthcare professionals and family can enhance the level of confidence among pregnant women regarding their engagement in Covid-19 vaccination.